RETINAL NERVE FIBER LAYER THICKNESS ASSOCIATED WITH SEVERITY OF DIABETIC PERIPHERAL NEUROPATHY IN DIABETES MELLITUS TYPE 2 - Putri, Mutiara Kristiani; Arfan, Muhammad; Rahmasari, Herisa; Dewi, Nadia Artha; Rosandi, Rulli; Kurniawan, Shahdevi Nandar (International Journal of Retina, 2025)
Purpose: To identify whether the Retinal Nerve Fiber Layer is useful in detecting severity of peripheral neurodegeneration in diabetic patients Methods: A cross-sectional study was conducted. 36 people were enrolled in this study which is divided into two groups. 18 people with type 2 diabetes mellitus (DM) with Diabetic Peripheral Neuropathy (DPN) and 18 people with type 2 DM non-DPN. All subjects were 40-60 years old, and the best corrected visual acuity was better than 0,2 logMAR. An Optical Coherence Tomography (OCT) examination was carried out to determine the Retinal Nerve Fiber Layer (RNFL) thickness, and an Electroneuromyography examination was applied to establish a diagnosis of DPN. Data were analyzed with independent T-test and Spearman correlation analysis. Results: The average RNFL thickness in the DM with DPN was thinner than the RNFL thickness in the DM non-DPN group (100.22 ± 38; vs 102.61±9.11; p 0.444). At temporal quadrant and nasal quadrant, RNFL was also thinner in DM DPN group than DM non-DPN group (71.78±12.21, vs 76.33 ± 8.53, p 0.203; and 75.11±11.38 vs 77.39 ± 14, p 0.596). Sural and tibial amplitude (14.44±2.87 and 6.85± 4.98) , were the most significant predictor values in determining the severity of DPN (p=0.000). Average, temporal, and nasal RNFL thinning has an inverse association with DPN severity (r=-0,285; -0,258;and -0,126) Conclusion: RNFL was thinner at average, temporal, nasal quadrant in the DM group with DPN compared to DM non-DPN group. RNFL thickness has an inverse association with the severity of the DPN although they were not statistically significant. Keywords: Diabetes Mellitus, Diabetic Peripheral Neuropathy, Retinal Nerve Fiber Layer